Análisis de las marcas blancas o propias, considerando específicamente el mercado de productos alimenticios - Ramírez Romero, Elizabeth Del Cisne (2016)
The Organic Law on Control of Market Power establishes sanction mechanisms to avoid unfair competition, including within them, those made through intellectual property. On October 13, 2011, Ecuador was one of the last countries in Latin America to have antitrust legislation to enact the Organic Law for the Regulation and Control of Market Power, the main objective of the law, commonly referred to as " Antitrust Law " as defined by its first article, avoid, prevent, correct, eliminate and punish the abuse of economic operators with market power. Its implementation involves all economic operators, whether public or private, domestic and foreign, with or without profit, which actually or potentially engage in economic activities in all or part of the Ecuadorian territory. Through this project we proceeded to investigate the private label products also known as store brands or own brands, focusing specifically in foodstuffs, this due to the significant increase of these products exhibited in major supermarkets in our country, which entered our market since 2006 having good acceptance and rapid growth because its price is lower in relation to industrial brands. White markings are an alternative to the consuming public and more than 90 % of these products are of national industry. The private label products are produced either by a retailer or the same belonging establishment trade group where they are marketed , using as a commercial name the name of the establishment such as the brands of " SUPERMAXI " which generates confidence to buy the product and not invest in advertising generate superior returns. The intent of this study is to determine whether the relationship between values of private labels satisfies the public consumer and whether those marks met the necessary requirements for marketing through a healthy competition in the Ecuadorian market. In most cases the private label products satisfy the consuming public as to its quality and its price represent a certain amount of savings, which makes the customer when choosing certain products acquire supermarket private label products, there are also a certain group of consumers who prefer to buy industrial products for its renowned quality brands although its price is higher.